Blood in Their Eyes : The Elaine Race Massacres of 1919 - Stockley, Grif (Book collections on Project MUSE., 2001)
"Grif Stockley tells the full story of this incident for the first time. Also a lawyer, he weighs the evidence in letters, interviews, newspapers, and trial transcripts. He makes a clear and powerful case that white mobs and federal soldiers murdered black citizens of Elaine."--Jacket